Life-threatening Dermatologic Adverse Events in Oncology - Rosen, Alyx C. (2014)
BACKGROUND: The incidence of life-threatening toxicities such as Stevens-Johnson syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are inconsistently reported. The potential association of anticancer agents with SJS or TEN has not been systematically investigated. METHODS: We searched the literature (Ovid:1950-June 2013 and PubMed:1948-June 2013) using terms for SJS/TEN and anticancer therapy. Primary case reports, case series, and clinical trials were included. Additionally, MedWatch, Food and Drug Administration Adverse Event Reporting System (FAERS), was searched (1968-August 2012) for SJS/TEN reports associated with anticancer therapies. Proportional reporting ratios (PRR>2, N>3) and empirical Bayes geometric mean (EBGM>2, N>3, lower 95% confidence interval (EBGM(0.05) >2) were used as thresholds to constitute a signal of association between SJS/TEN and anticancer drugs. RESULTS: There were 45 SJS and 37 TEN cases associated with 17 and 22 anticancer drugs in the literature, respectively. Among cases in FAERS, significant signals were associated with SJS for bendamustine and with TEN for bendamustine, busulfan, chlorambucil, fludarabine, lomustine, and procarbazine . CONCLUSION: Several drugs reported in published literature to be associated with SJS/TEN were not found to have significant signals in FAERS. Proactive pharmacovigilance to detect and define safety signals serves to assist oncology practitioners in the recognition of possible, yet uncommon, serious and/or life-threatening skin reactions.